Problemas
Progress The movement of the he progress bor may be uneven because questions can be worth more or less Including zerci depending a Factor: x^2-2x-63 (x-9)(x+2) (x+9)(x-7) (x-2)(x+9) (x-9)(x+7)
Roztwór
Sara
maestro · Tutor durante 5 años
4.2
(278 Votos)
Respuesta
To factor the quadratic expression
, we need to find two numbers that multiply to
and add up to
.Let's analyze the given options:1. \((x-9)(x+2)\) - Multiplying: \((x-9)(x+2) = x^2 + 2x - 9x - 18 = x^2 - 7x - 18\) - This does not match
.2. \((x+9)(x-7)\) - Multiplying: \((x+9)(x-7) = x^2 - 7x + 9x - 63 = x^2 + 2x - 63\) - This does not match
.3. \((x-2)(x+9)\) - Multiplying: \((x-2)(x+9) = x^2 + 9x - 2x - 18 = x^2 + 7x - 18\) - This does not match
.4. \((x-9)(x+7)\) - Multiplying: \((x-9)(x+7) = x^2 + 7x - 9x - 63 = x^2 - 2x - 63\) - This matches
.Therefore, the correct factorization is \((x-9)(x+7)\).